Anatomic variations of the renal arteries from a local study population using 3D computed tomography angiography reconstruction images from a reference hospital in Cali, Colombia (2016)
With the advances in the new image techniques and 3D modeling, angiography computed tomography (A-CT) has became a very useful image for studying vessels. Renal artery (RA) variations are common, and have a clinical relevance in pre-operative planning. There are several descriptive studies made in high income countries, but there are not many in middle and low income countries. Our objective was to describe prevalence of RA variations in a study population in Cali, Colombia. Methods: A database was made from a selection of A-CT 3D images from January 1, 2012 to September 30, 2014, from which the RA could be; visualized. Patients under 18 were excluded, also with no 3D A-CT, or not of; Colombian nationality. Frequencies, percentages were calculated using; Excel. Results: A total of 560 patients were selected, from which 296 fulfilled all criteria. The most common causes of performing the A-CT were pathologies of the Aorta. Variations of the RA were present in 52% of the patients, 54% were man, 77% had unilateral variation and 33% had bilateral variations, 58% in the right side. The two most common variations were extra Renal arteries (hiliar and polar) seen in 70% of the patients. Conclusions: Prevalence of RA can be as normal as the usual anatomy, more commonly found in men, unilateral and in the right side. The most common variations are accessories arteries to the polar zone and the renal hilium, but early division (double and triple) arteries are also common.